Shopeepay later in Indonesia: Navigating credit and payment issues in digital markets - Bujang Ali; Muhammad Doing; Fitriani Fitriani (Institute Of computer Science (IOCS), 2024)
This research seeks to comprehend ShopeePay Later credit in Indonesian laws and regulations and examine the dispute resolution mechanism for Financial Technology Peer to Peer Lending using ShopeePay Later. The normative juridical and economic law approach analyzes applicable laws and regulations, statistical data, case studies, and economic literature. Legal hermeneutic analysis interprets and applies legal documents to ShopeePay Later. The research shows that ShopeePay Later must follow Indonesian law and economics, including payment failure and sanctions. According to Law no. 30 of 1999, legal protection for users of this service is divided into preventive and repressive forms, with an emphasis on preventive measures and preparation of effective dispute resolution mechanisms like Alternative Dispute Resolution (APS).